HUBUNGAN KATARAK DENGAN OBAT ANTIHIPERTENSI - Aditya Putra Setia Ardana (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Cataract is opacity of crystalline lens. It usually occurs as a result of the aging process but can arise at birth (congenital cataracts). In Indonesia estimated that every minute one person becomes blind. The main causes of blindness are cataract (0.78%), glaucoma (0.20%), refractive errors (0.14%), and other diseases associated with aging (0.38%). The correlated between the different classes of antihypertensive drugs and cataract is biologically plausible. some classes of antihypertensive known to regulate specific ion channels in the lens epithelium. As the transparancy of the lens depends on the balance of electrolytes in the epithelium of the lens and the lens fibers, allows the use of these drugs can alter the physiology of normal lens into a cataract. This study was require to determine the correlated of cataract occurrence with the use of antihypertensive drugs. Methods: This research was a correlative analytic with cross sectional approach. Samples were 83 people aged â‰¥ 40 years in the village of Brajan, Kasihan, Bantul and Sleman Sedayu village already inspected cataracts and history of antihypertensive drug use. Analysis of study data using regression test with Chi Square method. Result: The number of respondents who consumed antihypertensive drug and cataracts were 39 respondents (47%) and respondents who consumed antihypertensive drug and not cataracts were 5 respondents (6%). While the number of respondents who were not consume antihypertensive drug and cataracts were 36 respondents (43.4%) and the respondents were not consume antihypertensive drug and not cataracts were 3 respondents (3.6%). On the results of Chi Square analysis showed that there was no significant association between cataract with antihypertensive drug consumption because p = 0.427, which means that p> 0.05. Conclusions : There was no relationship between cataract with antihypertensive drug consumption